1983
DOI: 10.1111/j.1365-2133.1983.tb03993.x
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind study of 1% metronidazole cream versus systemic oxytetracycline therapy for rosacea

Abstract: In a randomized double-blind trial fifty-one patients with rosacea were treated for 2 months with either I% metronidazole cream and placebo tablets or with 250 mg oxytetracycline tablets taken twice daily, and placebo cream (the cream base). The patients were assessed before and at the end of the trial, using the following criteria: (1) overall clinical assessment, (2) lesion counts, (3) degree of erythema, (4) independent photographic evaluation, (5) patients' opinion. An improvement was shown in 90% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 3 publications
2
32
0
2
Order By: Relevance
“…Since no change occurred in telangiectasia and rhinophyma, we thought that permethrin 5% cream and metronidazole 0.75% gel had no effect on telangiectasia and rhinophyma and, therefore, did not make any statistical analysis of telangiectasia and rhinophyma scores. Our finding that metronidazole 0.75% gel did not have any effect on telangiectasia and rhinophyma was consistent with the results of previous studies [4, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29]. …”
Section: Discussionsupporting
confidence: 83%
“…Since no change occurred in telangiectasia and rhinophyma, we thought that permethrin 5% cream and metronidazole 0.75% gel had no effect on telangiectasia and rhinophyma and, therefore, did not make any statistical analysis of telangiectasia and rhinophyma scores. Our finding that metronidazole 0.75% gel did not have any effect on telangiectasia and rhinophyma was consistent with the results of previous studies [4, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29]. …”
Section: Discussionsupporting
confidence: 83%
“…Metronidazole also reduced erythema scores significantly compared with placebo in patients with rosacea [66]. Topical metronidazole therapy was as effective as oral tetracycline in reducing the number of inflammatory lesions and the degree of erythema in patients with mild to severe rosacea treated for 8–9 weeks [71]. Metronidazole gel was more effective than placebo in maintaining remission in patients with rosacea [72].…”
Section: Topical Therapymentioning
confidence: 99%
“…70) It is therefore considered that the potential for drug related systemic side effects following topical application of metronidazole is extremely low. 8,61,64) In our study, we did not observe any systemic side effects in any of patients following 6 weeks of treatment, indicating that the metronidazole was not absorbed through the skin sufficient to cause systemic side effects, which is a desired condition for topically applied drugs.…”
Section: Discussionmentioning
confidence: 83%
“…6,7) Topical application of metronidazole was shown to be as effective as systemic antibiotic therapy. 8,9) Metronidazole is particularly effective against papules and pustules and is a well-tolerated alternative to oral antibacterials. The exact mechanism by which topical metronidazole reduces inflammatory lesions and erythema in rosacea is unknown; it is suggested that its anti-inflammatory effect may be due to its antioxidant action.…”
mentioning
confidence: 99%